THE FEATURES OF STATISTICAL CHARACTERISTICS TERRORISM ON TRANSPORT - M. Karmanov; S. Kuzin (Вестник университета)
Terrorism in transport as a special type of terrorism has in fact become a multifaceted and rapidly spreading phenomenon of modern social life, which cannot and should not remain outside the field of statistical science and practice. It is unlikely that a statistical estimate of transport terrorism can be derived from one or more private indicators. This is likely to require a system of statistical indicators, where individual elements occupy a well-defined place and complement each other consistently. In this case, the number of terrorist acts committed in public transport, for a certain period of time or a year, as well as the damage caused to society should be taken into account.